Pengembangan Soal Berpikir Kritis Menggunakan Aplikasi Wondershare Quiz Creator Pada Materi Hidrolisis Garam - Irfandi Irfandi; Rosa Murwindra (JNANALOKA, 2022)
Critical thinking ability is one of the must-have abilities for students in 21st century learning. This study aims to develop critical thinking questions on salt hydrolysis material using the wondershare quiz creator application. This research is a Research and Development with the Plomp model. The research subjects are 20 students and 2 chemistry teachers in a small-scale trial. The instruments used are critical thinking questions, material expert validation sheets, media expert, and response questionnaires for teachers and students. Based on the results of the validation of questions by the material, evaluation, language, and practitioner experts, the validation results have a score of 90% for the material aspect, 96% for the construction aspect, and 94% for the language aspect with a category of Valid. For the results from the media expert are 90% on content substance aspect, 95% on learning design aspect, and 92% on display aspect with a category of Valid. As for the result of the small-scale trial of student responses, it obtained the score of 87% in the “very good” category. While the result of the teacher responses obtained the score of 87.92% in the category of “very good” as well. Based on these results, critical thinking questions on hydrolysis material are valid to be used as an instrument for assessing critical thinking ability.